Optimalisasi Perkembangan Emosional Anak Usia Dini - Nur Asiah Lubis; Fitria Nur Afni Siregar; Khadijah Khadijah; Annisa Zaini Rahmah (Departement of Mathematics Education, 2023)
Children's emotional development is important to develop from an early age. The development of children's social-emotional abilities aims to make children feel confident, Able to socialize with others, restrain their emotions if they are in a state according to the ability and level of development of the child. The purpose of this study is to describe efforts to optimize early childhood social and emotional development through the role of teachers can be in the form of learning program design activities to their implementation with children according to children's learning theory which is based on the jargon